Systematic approach to delivering prolonged field care in a prehospital care environment. Issue 2 (27th February 2020) - Smith, Michael; Johnston, K; Withnall, R
Abstract : Background: This article describes a novel patient care algorithm which provides a Role 1 (R1) medic with a structured approach to delivering prolonged field care (PFC) in a resource-limited environment. PFC is a vital component of the operational patient care pathway providing the continuum of care from completion of a primary survey to the delivery to hospital care. Future operational environments are likely to have more fragile or extended lines of communication, potentially delaying evacuation to hospital care. This delay may lead to increases in patient morbidity and mortality. Effective PFC offers an opportunity to improve patient outcomes and help mitigate against this risk. Methods: An initial prototype model of a PFC care process was developed using existing hospital-based guidance. A series of medical and trauma vignettes and best available evidence were used to refine the algorithm. Results: The algorithm has been designed be used in conjunction with patient specific clinical guidance making the approach generalisable for all patient groups. For UK military, clinical guidance is provided by clinical guidelines for operations. The algorithm can be downloaded into a convenient format to be used on mobile devices or printed as an aide memoire.